Using Elements of Hip-Hop to Promote Student Engagement (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Incorporating hip-hop into the classroom is an effective way to increase the engagement of students, especially in urban schools. The use of hip-hop in education has become more popular in recent years and is a tool that could potentially benefit many teachers. Several studies were looked at that showed positive outcomes when teachers communicated and interacted with their students in a culturally congruent manner. By incorporating hip-hop while student teaching, this author observed a noticeable increase in student engagement.